Electrochemical Reactions of Europium in H2O-H3PO4-DTPA System - Belqat, B.; EL Kacemi, K.; Belcadi, S. (Asian Journal of Chemistry, 2010)
The reduction of Eu(III) ions in phosphoric acid with or without diethylenetriamine-pentaacetic acid (DTPA) was studied by electrochemical analyses. Electrochemical reactions involved complexation and solvation processes of europium ions with DTPA species in phosphoric acid. The diffusion coefficient of Eu(III) species was determined in diffusion-flow media. The effect of the europium concentration and the solvent on the complexation reactions was discussed. In addition to electrochemical informations on Eu-H3PO4–DTPA system in solution, spectrophotometric investigation confirms the formation of complexing species.